2019
DOI: 10.1371/journal.pone.0219032
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to linkage to HIV care and treatment among female sex workers in a community-based HIV prevention intervention in Tanzania: A qualitative study

Abstract: BackgroundHIV-infected female sex workers (FSWs) have poor linkage to HIV care in sub-Sahara Africa.MethodsWe conducted 21 participatory group discussions (PGDs) to explore factors influencing linkage to HIV care among FSWs tested for HIV through a comprehensive community-based HIV prevention project in Tanzania.ResultsInfluences on linkage to care were present at the system, societal and individual levels. System-level factors included unfriendly service delivery environment, including lengthy pre-enrolment s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…26,27 Poor ART uptake due to distance in rural areas has been reported in other studies, 9,28 besides the limitations relating to healthcare infrastructures, eg, where there is no privacy and or a shortage of voluntary counselling and testing services. 29,31 Availability of alternative care providers, especially in rural settings, is another limiting factor for ART uptake in many countries in SSA. 29 For instance, one study done in rural Tanzania reported the preference for traditional medicine as a major barrier to ART in children.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Poor ART uptake due to distance in rural areas has been reported in other studies, 9,28 besides the limitations relating to healthcare infrastructures, eg, where there is no privacy and or a shortage of voluntary counselling and testing services. 29,31 Availability of alternative care providers, especially in rural settings, is another limiting factor for ART uptake in many countries in SSA. 29 For instance, one study done in rural Tanzania reported the preference for traditional medicine as a major barrier to ART in children.…”
Section: Discussionmentioning
confidence: 99%
“…In turn both material access getting to the clinic (e.g. transport, distance, cost) [37,38] and psychosocial dynamics within the clinic (e.g. how groups do or do not feel respected and well-treated) will both be important issues to attend to as LA ART rolls-out across distinct settings [37][38][39][40][41].…”
Section: Plos Onementioning
confidence: 99%
“…transport, distance, cost) [37,38] and psychosocial dynamics within the clinic (e.g. how groups do or do not feel respected and well-treated) will both be important issues to attend to as LA ART rolls-out across distinct settings [37][38][39][40][41]. These factors are also known barriers to retention in care and adherence to daily oral ART, [42][43][44] suggesting that while LA ART will alleviate many challenges to adherence, there will still be ongoing and important issues to attend to in order to optimize HIV outcomes [45].…”
Section: Plos Onementioning
confidence: 99%
“…In an effort to effort to address the HIV self-testing research gap in Tanzania for heterosexual men, the Tanzania Self-Testing Education and Promotion (Tanzania STEP) project for men was launched in 2018 [32]. Since then, the Government of Tanzania also started a national HIV self-testing demonstration project focused on men who have sex with men and female sex workers (FSWs) as part of Sauti (meaning "voice of the people"), a ve-year implementation science community-based HIV prevention program funded by the U.S. President's Emergency Plan for AIDS Relief and U.S. Agency for International Development (PEPFAR/USAID) [33,34]. The overall aim of the Tanzania STEP and national HIV selftesting demonstration projects was to generate country-speci c data on the implementation models, uptake, feasibility and acceptability HIV self-testing in order to inform policy development and future implementation and scale-up of HIV self-testing in Tanzania.…”
Section: Introductionmentioning
confidence: 99%